2017
DOI: 10.1177/2058460117743279
|View full text |Cite
|
Sign up to set email alerts
|

CT Dental Artifact: Comparison of an Iterative Metal Artifact Reduction Technique with Weighted Filtered Back-Projection

Abstract: BackgroundDental hardware produces streak artifacts on computed tomography (CT) images reconstructed with the standard weighted filtered back projection (wFBP) method.PurposeTo perform a preliminary evaluation of an iterative metal artifact reduction (IMAR) technique to assess its ability to improve anatomic visualization over wFBP in patients with dental amalgam or other hardware.Material and MethodsCT images from patients with dental hardware were reconstructed using wFBP and IMAR software and soft-tissue or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…Thereafter, a new reconstruction is performed based on the corrected sinogram, which results in a reduced incidence of metal artifacts in the reconstructed CBCT scan . However, the performance of such MAR methods depends strongly on the quality of the initial metal artifact segmentation, and is often limited by the introduction of secondary artifacts and incomplete metal artifact correction . As a consequence, metal artifacts remain a challenge in CAS.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, a new reconstruction is performed based on the corrected sinogram, which results in a reduced incidence of metal artifacts in the reconstructed CBCT scan . However, the performance of such MAR methods depends strongly on the quality of the initial metal artifact segmentation, and is often limited by the introduction of secondary artifacts and incomplete metal artifact correction . As a consequence, metal artifacts remain a challenge in CAS.…”
Section: Introductionmentioning
confidence: 99%
“…2,15,16 Further studies, using anthropomorphic phantoms, also demonstrated the efficacy of iMAR. 17,18 Patient-based studies with iMAR are only rarely described in the literature, 4,19 and only a few retrospective studies with iMAR on real patients have been published so far, [20][21][22] albeit no contouring studies for the pelvis or head and neck (H & N) region have been performed. We used the iMAR algorithm for our study.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies indicated a superior reduction of dental artifacts caused by dental hardware or diverse maxillofacial metal implants when several MAR algorithms from major vendors were used, compared with standard reconstruction. [24][25][26][27][28][29] However, MAR algorithms may introduce new artifacts into the image. These new artifacts can appear as defects or blurring around metal hardware in the bone window.…”
Section: Discussionmentioning
confidence: 99%
“…These new artifacts can appear as defects or blurring around metal hardware in the bone window. 26,27 Recently, several clinical studies reported that the combination of spectral detector CT (or dualenergy CT) with virtual monoenergetic images and MAR provided optimal artifact reduction and improved diagnostic imaging assessments in patients with dental implants and bridges or metallic dental prostheses. 36,37 As noted previously, the MBIR algorithm is a revolutionary reconstruction technology that uses various models and repeats the subtraction of original raw data after forward projection to yield a reconstructed image that differs minimally from the raw data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation